Methanotroph activity and connectivity between two seep systems north off Svalbard - de Groot, Tim R.; Kalenitchenko, Dimitri; Moser, Manuel; Argentino, Claudio; Panieri, Giuliana; Lindgren, Matteus; Dølven, Knut Ola; Ferré, Benedicte; Svenning, Mette M.; Niemann, Helge (Frontiers in Earth Science, 2024)
Understanding methane flux dynamics in Arctic cold seep systems and the influence of oceanic currents on microbial methane-oxidizing bacteria (MOB) is crucial for assessing their impact on Arctic methane emissions. Here, we investigate methane dynamics and associated microbial communities at two cold seep areas, Norskebanken and Hinlopen Trough, North of Svalbard. Methane concentrations and methane oxidation rates (MOx) were measured in bottom and surface waters, with higher values observed in bottom waters, particularly at Hinlopen Trough. Dominant water column MOB clusters were Milano−WF1B−03 and Methyloprofundus. Methane availability drove MOx activity, as indicated by higher concentrations in bottom waters and sediments where MOx was elevated, too. Sediment MOB communities varied among locations, with Hinlopen featuring higher diversity and abundance. Similarities between sediments and water column MOBs suggest potential recruitment from sediments, possibly via a bubble shuttle mechanism. In addition, bottom water MOB community composition also showed similarities between the Norskebanken and Hinlopen seeps, implying an exchange of water column microbes between the two seep areas, which may likely be driven by the regional current regime. Together, our results show that bubble-mediated transport and translocation via currents are important processes shaping the community structure and efficiency of the microbial methane filter in the water column.